Il Vocabolario del romanesco contemporaneo, una nuova realtà tra i dizionari dialettali - Giovanardi, Claudio (Quaderni Veneti)
The essay concerns the Vocabolario del romanesco contemporaneo edited by Paolo D'Achille and Claudio Giovanardi (2023). Of this vocabulary, the structure of the headwords, the characteristics of the lemmary and the way in which literary examples have been included are presented. There is also a focus on the presence of neologisms and words that are archaic but still alive in the knowledge of speakers. Particular attention is given to the innovative contribution of the language of young people. The vocabulary includes dialect words, but also words that are used in Rome with a special meaning, different from what they have in standard Italian.